2023
DOI: 10.1128/spectrum.00566-23
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IMP Dehydrogenase as a Potential Target for Anti-Mpox Virus Agents

Abstract: Mpox is a zoonotic disease caused by infection with the mpox virus, and a worldwide outbreak occurred in May 2022. The smallpox vaccine has recently been approved for clinical use against mpox in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…However, an intercell type variation in efficacy of TFT could be observed (Figure 1C). In DF, TFT inhibited mpox virus with IC 50 values comparable to previously described TFT efficacy in Vero cells 10 as well as against other orthopoxviruses. 11 In contrast, TFT displayed twofold lower potency in keratocytes (mean IC 50 values 1.11 µM) and HConEpiC (mean IC 50 values 0.95 µM) in comparison to DF (mean IC 50 values 0.42 µM).…”
Section: Tft Efficacy In Ophthalmic Cell Modelssupporting
confidence: 80%
See 2 more Smart Citations
“…However, an intercell type variation in efficacy of TFT could be observed (Figure 1C). In DF, TFT inhibited mpox virus with IC 50 values comparable to previously described TFT efficacy in Vero cells 10 as well as against other orthopoxviruses. 11 In contrast, TFT displayed twofold lower potency in keratocytes (mean IC 50 values 1.11 µM) and HConEpiC (mean IC 50 values 0.95 µM) in comparison to DF (mean IC 50 values 0.42 µM).…”
Section: Tft Efficacy In Ophthalmic Cell Modelssupporting
confidence: 80%
“…TFT is a nucleoside analog, which has been approved for other ophthalmic conditions like herpes simplex keratitis 2 . A recent in vitro study demonstrated the antiviral efficacy of TFT against mpox infection in Vero cells 10 . However, the efficacy of antiviral drugs may differ between laboratory cell lines and primary cells derived from relevant tissues 17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation